Multi-body model of a bobsleigh: Comparison with experimental data - Braghin, F.; Cheli, F.; Donzelli, M.; Melzi, S.; Sabbioni, E. (Multibody System Dynamics, 2011)
Bobsleigh is a winter sport in which teams make timed runs down narrow, twisting, banked, iced tracks in gravity-powered sleds. To win the race, it is of great importance to have a sled that is optimized from both the sliding and the aerodynamic point of view. However, also typical vehicle parameters, such as the weight distribution and the inclination of the steering axis, play an important role. In fact, being the friction coefficient between skates and ice very small (approx. 0.04), a change in the weight acting on the front skates may significantly modify the steering feedback of the driver thus highlighting his/her driving ability. Better trajectories imply less correction on the steering axis, and thus better performances. The inclination of the steering axis, instead, generates a torque similar to the self-aligning torque produced by road vehicle tires thus stabilizing the front skates and requiring less control actions to the sled driver.